Use of the EVARREST patch for penetrating cardiac injury. (August 2020) - Romero-Velez, Gustavo; Kaban, Jody M.; Chao, Edward; Lewis, Erin R.; Stone, Melvin E.; Teperman, Sheldon; Reddy, Srinivas H.
Abstract: Penetrating cardiac injuries have a pre-hospital mortality of 94% with a subsequent in-hospital mortality of 50% among initial survivors (Leite et al., 2017 [1]). The Western Trauma Association (WTA) guidelines recommend resuscitative thoracotomy (RT) for patients with penetrating torso trauma and less than 15 min of cardiopulmonary resuscitation (CPR) Burlew et al. (2012) [2]. Penetrating cardiac injuries are classically repaired using skin-stapling devices and/or suture repair with or without pledgets (Wall et al., 1997 [3]). In this study, we present a case of penetrating cardiac injury where all the aforementioned techniques failed, and a new approach was explored. A fibrinogen/thrombin patch was used in this clinical setting, which is an off-label use of the product, we here present our encouraging outcome.